Psychological Well-being Family Affected by Tidal Flood in Pekalongan City - Indar Widowati; Afiyah Sri Harnany; Zaenal Amirudin (Universitas Ahmad Dahlan, 2020)
Tidal floods affect the surrounding community not only on social, economic, environmental aspects, but also psychological aspects. This phenomenon becomes very important for families in achieving psychological well-being. The purpose of this study was to analyze the psychological well-being of families affected by tidal flooding. Quantitative methods was used in this research with cross sectional study approaches. A total of 84 respondents were taken by purposive sampling. Spearman Rank and Kruskal Wallis correlations was used for data analysis. The result showed that the psychological well-being of respondents averaged 159 197.39 with the lowest value and the highest value of 228. The Kruskal Wallis test results obtained Ï: 0.340> 0.05, meaning that there is no difference in psychological well-being in the three villages. The psychological well-being of families affected by tidal floods is in the low category, so it needs guidance, and cooperation between related institutions in handling psychological aspects.